Предмет: Алгебра,
автор: tacherbeztrusov
Упростите выражение: (2x-1)*(4x²+2x+1)-4x*(2x²-3) при х=0,5 равно 5. ПОМОГИТЕ У МЕНЯ СОЧ
Ответы
Автор ответа:
1
Ответ:
5
Объяснение:
1. действие: (2x-1)*(4x²+2x+1)-4x*(2x²-3)=8x^3-1-8x^3+12x=-1+12x
2. действие: заменяем x на 0,5
3. действие: -1+12*0,5=-1+6=5
tacherbeztrusov:
Спасибо лучший)
Похожие вопросы
Предмет: Русский язык,
автор: Marchl
Предмет: Русский язык,
автор: aelitaponomare
Предмет: Окружающий мир,
автор: хилая
Предмет: Математика,
автор: Miya688